Improving care standards for patients with spinal trauma combining a modified e-Delphi process and stakeholder interviews: a study protocol. Issue 1 (19th January 2017) - Sharwood, Lisa N; Stanford, Ralph; Middleton, James W; Burns, Brian; Joseph, Anthony; Flower, Oliver; Rigby, Oran; Ball, Jonathon; Dhaliwal, Shelly
Abstract : Introduction: Around 300 people sustain a new traumatic spinal cord injury (TSCI) in Australia each year; a relatively low incidence injury with extremely high long-term associated costs. Care standards are inconsistent nationally, lacking in consensus across important components of care such as prehospital spinal immobilisation, timing of surgery and timeliness of transfer to specialist services. This study aims to develop 'expertly defined' and agreed standards of care across the majority of disciplines involved for these patients. Methods and analysis: A modified e-Delphi process will be used to gain consensus for best practice across specific clinical early care areas for the patient with TSCI; invited participants will include clinicians across Australia with relevant and significant expertise. A rapid literature review will identify available evidence, including any current guidelines from 2005 to 2015. Level and strength of evidence identified, including areas of contention, will be used to formulate the first round survey questions and statements. Participants will undertake 2–3 online survey rounds, responding anonymously to questionnaires regarding care practices and indicating their agreement or otherwise with practice standard statements. Relevant key stakeholders, including patients, will also be interviewed face to face. Ethics and dissemination: Ethics approval for this study was obtained by the NSW Population & Health Services Research Ethics Committee on 14 January 2016 (HREC/12/CIPHS/74). Seeking comprehensive understanding of how the variation in early care pathways and treatment can be addressed to achieve optimal patient outcomes and economic costs; the overall aim is the agreement to a consistent approach to the triage, treatment, transport and definitive care of acute TSCI victims. The agreed practice standards of care will inform the development of a Clinical Pathway with practice change strategies for implementation. These standards will offer a benchmark for state-wide and potentially national policy.